A CENTRALIDADE NA FAMÍLIA NO DISCURSO DA POLÍTICA DE ASSISTÊNCIA SOCIAL BRASILEIRA: imprecisões, continuidades e rupturas - Silva, Maria Jacinta Carneiro Jovino da (2012)
This thesis aims at analyzing the official discourse of the Brazilian Social Assistance Policy on the family and the idea of centrality in the family, from their key documents, both at the level of the general formulation and of the regulation and at the level of technical guidance and standardization of the socioassistencial services, within the period from 1999 to 2011. We seek to understand the contemporary family as a dynamic and contradictory whole, built by the historical, economic, cultural and social. That movement, and as an expression of the diversity and complexity of forms of family life. That movement produces changes in the major determinants of the construction of family concept: the patterns of sexuality and conjugality; the relations of consanguinity and filiation; the cohabitation; and family affection and solidarity. It discusses the approach of the family in demographic studies, highlighting the controversies and the influences of these studies in the Social Assistance Policy. We also analyze the building process of that policy, highlighting its contradictions, innovations and continuities. It discusses the social inequality in Brazil, showing how effective it is in the Brazilian families and among their different configurations.The conception of the Social Assistance Policy is captured within the conflict between the assistencialist tradition and the process of affirmation of rights, while we seeks to understand how the family is inserted into the process of setting up of that policy. Some advances in the legal conceptual field of the Social Assistance Policy of that are highlighted, as well as the limits of the social protection for the families and the key elements for the design of the policy: its specificity in social protection; the intersectionality; and its decentralization in the context of the SUAS. Finally, we analyze the official discourse of the Brazilian Social Assistance Policy, using the method of Discourse Analysis, seeking to understand how the family and the idea of centrality in the family appear as discursive guidelines of the main documents of that Policy: the Organic Law of Social Assistance; the first and second National Policy of Social Assistance (PNAS/1998; 2004), as well as the documents related to basic social protection and the special social protection of the Policy destined to families. In the official discourse of that policy, the family and the centrality in the family appear in an imprecise, diffuse and ambiguous way. The analysis of the documents led to the identification in that discourse of the social stability, the discontinuities, the ruptures, the unspoken and the interdict. The idea of centrality in the family appears in a different way: now it is announced, sometimes it is said, sometimes it is interdicted.